Effects of psychosocial and individual psychological factors on the onset of musculoskeletal pain: common and site-specific effects. Issue 8 (1st August 2003) - Nahit, E S; Hunt, I M; Lunt, M; Dunn, G; Silman, A J; Macfarlane, G J
Abstract : Objective: To determine whether adverse psychosocial and individual psychological factors increase the risk of pain across regional sites. Methods: A prospective study was conducted of newly employed workers from 12 diverse occupational groups. Near to the beginning of subjects' employment, details of work related psychosocial factors and individual psychological distress were obtained by means of a self completed questionnaire. Questionnaire follow up after 12 months provided data on these same exposures and ascertained pain at any of four anatomical sites: the low back, shoulder, wrist/forearm, and knee. Results: Of the original 1081 subjects, 829 (77%) provided full details at the one year follow up. Psychosocial work demands and high levels of individual psychological distress were found to have a common effect across sites. Psychological distress was associated with a doubling of the risk of reported pain (odds ratio = 2.1, 95% confidence interval 1.6 to 2.7), while aspects of job demand, poor support from colleagues, and work dissatisfaction were all associated with increased odds of reported pain onset of between 1.4 and 1.7. These effects were almost all common across the four regional pain sites. Conclusions: In cohorts of newly employed workers, certain work related psychosocial factors and individual psychological distress are associated with the subsequent reporting of musculoskeletal pain, and generally this effect is common across anatomical sites.